2014
DOI: 10.1155/2014/208590
|View full text |Cite
|
Sign up to set email alerts
|

Paternity Analysis of the Olive Variety “Istrska Belica” and Identification of Pollen Donors by Microsatellite Markers

Abstract: The leading olive variety in Slovenia is “Istrska belica” (Olea europaea L.), which currently represents 70% of all olive trees in productive orchards. Paternity analysis based on microsatellite markers was used for genotyping and identification of the potential pollen donors of “Istrska belica” and for assessing the proportion of self-fertilization in monovarietal olive orchards in the Slovene Istria. Seven microsatellite loci were used for genotyping thirty-one olive embryos from “Istrska belica” trees and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In particular, the use of microsatellite markers (SSR) is notoriously simply, relatively cheap, reliable, and specie-specific (Sefc et al, 2000; Carriero et al, 2002; Cipriani et al, 2002). In olive, they have been used for different purposes, such as cultivar identification (Alba et al, 2009), assessment of genetic diversity (Albertini et al, 2011), evaluation of relationships among cultivated and wild olives (Boucheffa et al, 2017), designation of geographic origin (Sarri et al, 2006; Montemurro et al, 2015), genetic mapping (De la Rosa et al, 2003), construction of core collections (Haouane et al, 2011), oil traceability (Pasqualone et al, 2013, 2016; Sabetta et al, 2017), paternity test (De La Rosa et al, 2004; Dìaz et al, 2007; Arbeiter Baruca et al, 2014), and evaluation of polyploidy level (Besnard and Baali-Cherif, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of microsatellite markers (SSR) is notoriously simply, relatively cheap, reliable, and specie-specific (Sefc et al, 2000; Carriero et al, 2002; Cipriani et al, 2002). In olive, they have been used for different purposes, such as cultivar identification (Alba et al, 2009), assessment of genetic diversity (Albertini et al, 2011), evaluation of relationships among cultivated and wild olives (Boucheffa et al, 2017), designation of geographic origin (Sarri et al, 2006; Montemurro et al, 2015), genetic mapping (De la Rosa et al, 2003), construction of core collections (Haouane et al, 2011), oil traceability (Pasqualone et al, 2013, 2016; Sabetta et al, 2017), paternity test (De La Rosa et al, 2004; Dìaz et al, 2007; Arbeiter Baruca et al, 2014), and evaluation of polyploidy level (Besnard and Baali-Cherif, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding crosses among diploid genotypes, surprisingly, Leccino wt became interfertile with its 2n mutants and, in addition, the 2n mutants also became interfertile among themselves (Table 2). Although pollen contamination during artificial pollination should be excluded, considering the accuracy of the method used in this experiment, the progeny parentage analysis by molecular approaches will be considered in the future, since some authors reported possible risk of contamination (Arbeiter et al, 2014;Díaz et al, 2007). Moreover, high fruit set was observed when the LD mutant was used as pollen donor and Leccino wt as female parent, while Leccino wt used as pollen donor proved to be less fertile (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…This method was later applied in several other tree species, for instance in Eucalyptus sp. (Cupertino et al, 2009) and in olives (Baruca-Arbeiter et al, 2014). Paternity testing was also used to identify pollen contamination rate, for instance in loblolly pine (Vidal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%